2014
DOI: 10.3892/or.2014.3212
|View full text |Cite
|
Sign up to set email alerts
|

The oxygen radicals involved in the toxicity induced by parthenolide in MDA-MB-231 cells

Abstract: Abstract.It has been shown that the sesquiterpene lactone parthenolide lowers the viability of MDA-MB-231 breast cancer cells, in correlation with oxidative stress. The present report examined the different radical species produced during parthenolide treatment and their possible role in the toxicity caused by the drug. Time course experiments showed that in the first phase of treatment (0-8 h), and in particular in the first 3 h, parthenolide induced dichlorofluorescein (DCF) signal in a large percentage of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…The anti-scavenging activity of these cultivars was positively correlated with both ascorbic acid and total polyphenol contents [30], albeit the authors did not explore the biochemical mechanism responsible for the observed effects. In this scenario, we recently started to explore the antioxidant and anti-aging properties of Sicilian mango extracts exploiting our knowledge in the study of oxidative stress and cell death induction in tumour systems [31,32,33,34,35,36,37]. Using fruit extract from the Kensington Pride cultivar grown and widely spread in Balestrate (Palermo) and other Sicilian rural areas, our preliminary results provided evidence that exocarp, mesocarp, and endocarp of mango can efficaciously counteract oxidative damage caused by ROS.…”
Section: Antioxidant Properties Of Mangifera Indica Lmentioning
confidence: 99%
“…The anti-scavenging activity of these cultivars was positively correlated with both ascorbic acid and total polyphenol contents [30], albeit the authors did not explore the biochemical mechanism responsible for the observed effects. In this scenario, we recently started to explore the antioxidant and anti-aging properties of Sicilian mango extracts exploiting our knowledge in the study of oxidative stress and cell death induction in tumour systems [31,32,33,34,35,36,37]. Using fruit extract from the Kensington Pride cultivar grown and widely spread in Balestrate (Palermo) and other Sicilian rural areas, our preliminary results provided evidence that exocarp, mesocarp, and endocarp of mango can efficaciously counteract oxidative damage caused by ROS.…”
Section: Antioxidant Properties Of Mangifera Indica Lmentioning
confidence: 99%
“…In this case we have tried using the probes in a 50% aqueous acetonitrile solution, which seems to work quire well, although perhaps not exactly as well as pure water. Both HPF and APF are taken up into cells so they can be used to detect the intracellular generation of HO • and ONOO - [56]. Although it was reported that SOSG is not taken up into cells, a subsequent report showed that it could bind to proteins and gain entry to cells [57], and it was reported to detect 1 O 2 in vivo in plant leaves [58].…”
Section: Singlet Oxygen Sensor Green (Sosg) and 4-hydroxyphenyl Fluormentioning
confidence: 99%
“…At the same time it showed low toxicity against normal cells. PN acts cytotoxically on MDA-MB231 cells, but at low doses it is not effective (60,61). Investigators have combined PN and SAHA in order to overcome the PN's deficiency (55).…”
Section: Hdac Inhibitors As Anti-cancer Agentsmentioning
confidence: 99%